Suppression of vortical turbulence in plasma in crossed electrical and magnetic fields due to finite lifetime of electrons and ions and due to finite system length - Maslov, V.I.; Levchuk, I.P.; Onishchenko, I.N.; Yegorov, A.M.; Yuferov, V.B. (Вопросы атомной науки и техники, 2015)
The dispersion equation, describing the instability development of vortex turbulence excitation in cylindrical plasma in crossed radial electric and axial magnetic fields with taking into account the longitudinal inhomogeneity and finite time of leaving of plasma electrons and ions from the system, has been derived. It is shown that the finite length of system time and finite time of system leaving of plasma electrons and ions leads to the appearance of the instability threshold and to decrease of growth rate of its development. Отримано дисперсійне рівняння, що описує розвиток нестійкості збудження вихрової турбулентності в циліндричній плазмі в схрещених радіальному електричному та поздовжньому магнітному полях з урахуванням поздовжньої неоднорідності і кінцевого часу залишання системи електронами та іонами плазми. Показано, що кінцева довжина системи і кінцевий час залишання системи електронами і іонами плазми призводять до появи порога нестійкості та зменшення інкремента її розвитку. Получено дисперсионное уравнение, описывающее развитие неустойчивости возбуждения вихревой турбулентности в цилиндрической плазме в скрещенных радиальном электрическом и продольном магнитном полях с учетом продольной неоднородности и конечного времени ухода электронов и ионов плазмы из системы. Показано, что конечная длина системы и конечное время покидания системы электронами и ионами плазмы приводят к появлению порога неустойчивости и уменьшению инкремента ее развития.